Hollow fiber electrode and method of making, flexible capacitor, flexible battery
Patent Information
- Application Number
- CN202611233874.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明的主要目的在于提供一种中空纤维电极及制备方法、柔性电容器、柔性电池,旨在解决传统柔性电极力学耐久性不足、离子传输效率低以及中空腔体功能单一的问题
[0016] This invention provides a hollow fiber electrode. The outer dense microporous region forms a "protective shell" structure with low porosity (10-30%) and small pore size (1-10 nm). During repeated bending and stretching, it effectively suppresses the generation and propagation of surface cracks. After 10,000 cycles under 50% tensile deformation, the capacitance retention rate increases from ~50% of the traditional structure to >85%. There are no obvious cracks on the fiber surface, and the mechanical properties and durability of the fiber are significantly improved. The intermediate gradient transition region realizes a continuous gradient change of the ion transport channel. After ions enter from the outer dense region, the transport resistance gradually decreases as the pore size gradually increases, avoiding the scattering and retention problems of ions at the pore interface in the traditional uniform pore structure. The effective ion conductivity is increased by 40-60%, and the ion transport efficiency is optimized. The inner hollow cavity not only serves as a "highway" for rapid ion transport, but also allows for direct injection of PVA/H2SO4 gel electrolyte, maximizing the contact area between the electrolyte and the electrode active material.
Smart Images

Figure CN122930729A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy materials and flexible energy storage devices, and particularly to a hollow fiber electrode and its preparation method, a flexible capacitor, and a flexible battery. Background Technology
[0002] With the rapid development of emerging fields such as smart wearable devices, flexible electronics, and the Internet of Things, the demand for flexible energy storage devices that combine high energy density, excellent mechanical flexibility, and long cycle life is becoming increasingly urgent.
[0003] Graphene, as a type of graphene, is composed of sp 2 Two-dimensional materials composed of a single atomic layer of hybrid carbon atoms are ideal for constructing high-performance flexible energy storage electrodes. However, traditional graphene preparation methods have many limitations: the Hummers redox method involves strong acid and strong oxidant treatment, generating a large amount of waste liquid and waste gas, and the conjugated structure of graphene is destroyed, resulting in a significant decrease in conductivity; the chemical vapor deposition (CVD) method is complex, costly, and difficult to scale up.
[0004] In terms of flexible electrode structure design, the existing technologies mainly have the following problems: (1) The ion diffusion path of traditional solid fiber electrodes is tens to hundreds of micrometers long, resulting in poor rate performance and low power density; (2) In traditional uniform porous structure electrodes, the electrolyte is difficult to fully wet the micropores, and the actual utilization rate of active materials is only 30-50%; (3) There is an inherent contradiction between high active material load and high mechanical flexibility, which is difficult to balance; (4) The outer surface of the fiber electrode lacks a dense protective structure, and surface cracks are easily generated during long-term bending and stretching, leading to the breakage of the conductive network and the degradation of electrochemical performance; (5) The hollow cavity of the existing hollow fiber electrode has a single utilization method, which fails to give full play to its unique advantages in electrolyte filling and electrode integration. In summary, traditional flexible electrodes have insufficient mechanical durability, low ion transport efficiency, and a single function of the hollow cavity. Summary of the Invention
[0005] The main objective of this invention is to provide a hollow fiber electrode and its preparation method, a flexible capacitor, and a flexible battery, aiming to solve the problems of insufficient mechanical durability, low ion transport efficiency, and limited functionality of traditional flexible electrodes with hollow cavities.
[0006] To achieve the above objectives, the present invention provides a hollow fiber electrode, which comprises, from the outside to the inside, the following components along the radial direction: The outer dense microporous region has a pore size of 1 nm to 10 nm and a porosity of 10% to 30%, and the outer dense microporous region forms a mechanical protective layer; An intermediate gradient transition region, wherein the pore size continuously transitions from 5nm to 10nm on the outer side to 50nm to 200nm on the inner side, forms an ion transport channel; and, An inner wall layer, in which a hollow cavity is formed, the inner diameter of which is 50μm to 200μm, is used to fill a gel electrolyte or to accommodate a zinc wire electrode. The hollow fiber electrode is made of graphene / polyaniline composite active material and thermoplastic polyurethane elastic (TPU) matrix.
[0007] In one embodiment, the outer dense microporous region is formed by phase separation of the sheath spinning solution, wherein the sheath spinning solution contains nano-calcium carbonate and fumed silica thickener; The nano-calcium carbonate has a particle size of 20 nm to 100 nm, and the mass of the nano-calcium carbonate is 2% to 5% of the total mass of the sheath spinning solution; the mass of the fumed silica is 0.3% to 0.8% of the total mass of the sheath spinning solution.
[0008] In one embodiment, the intermediate gradient transition region is formed by phase separation of an intermediate layer spinning solution, the intermediate layer spinning solution containing a polyethylene glycol pore-forming agent; The polyethylene glycol has a molecular weight of 2000 to 8000, and the mass of the polyethylene glycol is 8% to 15% of the total mass of the intermediate spinning solution.
[0009] In one embodiment, the inner wall layer is formed by phase separation of the core spinning solution, the core spinning solution containing a water-soluble pore-forming agent selected from sodium chloride or sodium bicarbonate, the mass of the water-soluble pore-forming agent being 8% to 15% of the total mass of the core spinning solution.
[0010] This invention also provides a method for preparing a hollow fiber electrode, comprising the following steps: Preparation of graphene / polyaniline composite active materials; A three-layer coaxial spinning solution was prepared, wherein the sheath spinning solution contains thermoplastic polyurethane, graphene / polyaniline composite active material, nano-calcium carbonate and fumed silica thickener; the middle layer spinning solution contains thermoplastic polyurethane, graphene / polyaniline composite active material and polyethylene glycol; and the core layer spinning solution contains thermoplastic polyurethane, graphene / polyaniline composite active material and water-soluble pore-forming agent. The core spinning solution, intermediate spinning solution and sheath spinning solution are simultaneously extruded into a coagulation bath using a three-layer coaxial spinneret. During the extrusion process, core coagulation solution or inert gas is introduced into the core layer to form a hollow cavity. After phase separation and pore-forming reaction, gradient porous hollow fiber is obtained. The gradient porous hollow fiber is subjected to post-processing and electrochemical deposition.
[0011] In one embodiment, the step of preparing the graphene / polyaniline composite active material includes: The graphene / polyaniline composite active material is produced by simultaneous mechanical exfoliation-in-situ polymerization using expanded graphite as raw material and aniline as both an intercalating agent and a polymerization monomer. The material is sheared at a speed of 10,000 rpm to 20,000 rpm for 0.5 h to 2 h in a high-speed shear field, which exfoliates the expanded graphite into graphene and polymerizes aniline in situ on the graphene surface. The mass loading of polyaniline in the graphene / polyaniline composite active material is 30%–60%.
[0012] In one embodiment, in the step of simultaneously extruding the core spinning solution, the intermediate spinning solution, and the sheath spinning solution into a coagulation bath using a three-layer coaxial spinneret, the coagulation bath is an acidic aqueous solution containing ammonium persulfate, wherein the concentration of H2SO4 in the acidic aqueous solution is 0.5 M to 2 M, and the concentration of ammonium persulfate is 0.02 M to 0.1 M. The spinning process parameters are as follows: core layer advance rate is 40 mL / h to 60 mL / h, intermediate layer advance rate is 50 mL / h to 70 mL / h, sheath layer advance rate is 70 mL / h to 90 mL / h, and coagulation bath temperature is 20℃ to 30℃.
[0013] In one embodiment, the electrochemical deposition process includes: The gradient porous hollow fiber was used as the working electrode and placed in a 1M H2SO4 electrolyte containing aniline monomer. A polyaniline nanoarray was electrochemically deposited on the outer surface of the fiber using a constant potential method. The concentration of aniline monomer in the electrolyte is 0.03 M to 0.08 M, the deposition potential is +0.6 V to +1.0 V, and the deposition time is 10 min to 20 min.
[0014] The present invention also provides a flexible capacitor comprising two hollow fiber electrodes as described above, wherein a PVA / H2SO4 gel electrolyte is infused into the hollow cavity of the hollow fiber electrode by capillary action, and a PVA / H2SO4 gel electrolyte layer is coated on the outer surface of the hollow fiber electrode. The two hollow fiber electrodes are arranged in parallel or intertwined and encapsulated with PDMS or gel electrolyte.
[0015] The present invention also provides a flexible battery, comprising a hollow fiber electrode as described in any one of the above descriptions, wherein the hollow fiber electrode is a positive electrode carrier, the outer surface of the hollow fiber electrode is loaded with a graphene / polyaniline / ammonium vanadate ternary composite positive electrode material, a zinc wire electrode is inserted into the hollow cavity of the hollow fiber electrode as a negative electrode, and a ZnSO4 aqueous electrolyte is injected into the hollow fiber electrode to form a flexible battery with a coaxial structure.
[0016] This invention provides a hollow fiber electrode. The outer dense microporous region forms a "protective shell" structure with low porosity (10-30%) and small pore size (1-10 nm). During repeated bending and stretching, it effectively suppresses the generation and propagation of surface cracks. After 10,000 cycles under 50% tensile deformation, the capacitance retention rate increases from ~50% of the traditional structure to >85%. There are no obvious cracks on the fiber surface, and the mechanical properties and durability of the fiber are significantly improved. The intermediate gradient transition region realizes a continuous gradient change of the ion transport channel. After ions enter from the outer dense region, the transport resistance gradually decreases as the pore size gradually increases, avoiding the scattering and retention problems of ions at the pore interface in the traditional uniform pore structure. The effective ion conductivity is increased by 40-60%, and the ion transport efficiency is optimized. The inner hollow cavity not only serves as a "highway" for rapid ion transport, but also allows for direct injection of PVA / H2SO4 gel electrolyte, maximizing the contact area between the electrolyte and the electrode active material. Attached Figure Description
[0017] Figure 1 This is a SEM image of the cross-section of the hollow fiber electrode provided in the embodiment of the present invention; Figure 2 This is a schematic diagram of the structure of the flexible capacitor filled with gel electrolyte provided in the embodiment of the present invention; Figure 3 These are the CV and GCD curves of a flexible capacitor.
[0018] Explanation of icon numbers: 100. Hollow fiber electrode; 1. Outer dense microporous region; 2. Intermediate gradient transition region; 3. Inner wall layer.
[0019] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0021] It should be noted that if the embodiments of the present invention involve directional indicators (such as up, down, left, right, front, back, etc.), the directional indicators are only used to explain the relative positional relationship and movement of the components in a certain specific posture (as shown in the figure). If the specific posture changes, the directional indicators will also change accordingly.
[0022] Furthermore, if the embodiments of this invention involve descriptions such as "first" or "second," these descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of those features. Additionally, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, solution B, or a solution where both A and B are satisfied simultaneously. Furthermore, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or impossible to implement, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.
[0023] Please see Figure 1 This invention provides a hollow fiber electrode 100, which, along the radial direction, comprises, from the outside to the inside, an outer dense microporous region 1, an intermediate gradient transition region 2, and an inner wall layer 3. The outer dense microporous region 1 has a pore size of 1 nm to 10 nm and a porosity of 10% to 30%, forming a mechanical protective layer. The intermediate gradient transition region 2 has a pore size that continuously transitions from 5 nm to 10 nm on the outer side to 50 nm to 200 nm on the inner side, forming an ion transport channel. A hollow cavity is formed within the inner wall layer 3, with an inner diameter of 50 μm to 200 μm, and is used for injecting gel electrolyte or accommodating zinc wire electrodes. The hollow fiber electrode 100 is made of graphene / polyaniline composite active material and thermoplastic polyurethane elastic matrix.
[0024] This invention provides a hollow fiber electrode 100. The outer dense microporous region 1 forms a structure similar to a "protective shell," with low porosity (10-30%) and small pore size (1-10 nm). During repeated bending and stretching, it effectively suppresses the generation and propagation of surface cracks. After 10,000 cycles under 50% tensile deformation, the capacitance retention rate increases from ~50% of the traditional structure to >85%. There are no obvious cracks on the fiber surface, and the mechanical properties and durability of the fiber are significantly improved. The intermediate gradient transition region 2 realizes a continuous gradient change in the ion transport channel. After ions enter from the outer dense region, the transport resistance gradually decreases as the pore size gradually increases, avoiding the scattering and retention problems of ions at the pore interface in the traditional uniform pore structure. The effective ion conductivity is increased by 40-60%, and the ion transport efficiency is optimized. The inner hollow cavity can not only serve as a "highway" for rapid ion transport, but also directly inject PVA / H2SO4 gel electrolyte, maximizing the contact area between the electrolyte and the electrode active material.
[0025] The dense micropores in the outer layer of this invention improve the mechanical durability of the fiber, the intermediate gradient transition optimizes ion transport efficiency, and the hollow inner layer expands the electrolyte filling and electrode integration functions. The assembled flexible supercapacitor retains >88% capacity after 15,000 cycles under 50% tensile deformation; the aqueous zinc-ion battery has a specific capacity of 580 mAh / g and retains >82% capacity after 2,000 cycles.
[0026] Furthermore, the outer dense microporous region 1 is formed by phase separation of the sheath spinning solution, which contains nano-calcium carbonate and fumed silica thickener; the nano-calcium carbonate has a particle size of 20 nm to 100 nm, and the mass of the nano-calcium carbonate is 2% to 5% of the total mass of the sheath spinning solution; the mass of the fumed silica is 0.3% to 0.8% of the total mass of the sheath spinning solution. The dense microporous outer layer acts as the "armor" of the fiber, effectively withstanding the mechanical stress during textile processing (such as weaving and winding), preventing structural failures such as fiber breakage and cracking during subsequent processing or use. Through the synergistic thickening effect of nano-calcium carbonate (2%–5%) and fumed silica (0.3%–0.8%), the viscosity and phase separation kinetics of the sheath spinning solution can be precisely adjusted without changing the main polymer formulation, thereby achieving controllable adjustment of pore size and porosity. The dense outer structure also serves as an outer surface barrier for the electrode, playing a stress buffering role during repeated bending of flexible devices, extending the cycle life of the electrode and device.
[0027] In addition, the intermediate gradient transition zone 2 is formed by phase separation of the intermediate layer spinning solution, which contains polyethylene glycol pore-forming agent; the molecular weight of the polyethylene glycol is 2000-8000, and the mass of the polyethylene glycol is 8%-15% of the total mass of the intermediate layer spinning solution. Unlike the step-like changes in pore size between layers in traditional multilayer structures (with significant interlayer resistance), the continuous gradient transition achieves a smooth change in pore size from 5 nm to 200 nm, eliminating interlayer interfaces and reducing resistance to ion transport across layers. The intermediate gradient transition region acts as a "bridge" between the outer dense region and the inner hollow cavity. Its gradual pore size distribution ensures sufficient specific surface area (small pore side) for loading active materials and electrochemical reactions, while also providing unobstructed ion transport paths (large pore side) for rapid diffusion of electrolyte ions, achieving a balance between "high specific surface area" and "fast ion transport". By selecting different molecular weights (2000–8000) and different contents (8%–15%) of PEG, the pore size range, gradient steepness, and overall porosity of the gradient transition region can be flexibly controlled to meet the different requirements of electrode structure for different application scenarios.
[0028] Furthermore, the inner wall layer is formed by phase separation of the core layer spinning solution. The core layer spinning solution contains a water-soluble pore-forming agent, selected from sodium chloride or sodium bicarbonate, with the mass of the water-soluble pore-forming agent being 8%–15% of the total mass of the core layer spinning solution. Sodium chloride or sodium bicarbonate, as a water-soluble pore-forming agent, dissolves rapidly in the aqueous phase coagulation bath and is washed out. Combined with the coagulation liquid or inert gas introduced into the core layer, the continuity and regularity of the hollow cavity are ensured, and the inner diameter can be controlled within the range of 50–200 μm. The continuous hollow cavity provides physical space for the functionalization of the electrode—it can be filled with gel electrolyte for solid-state supercapacitors, or nested with zinc wire electrodes for aqueous zinc-ion batteries, realizing the universal application of the same electrode structure in different energy storage devices. The inner wall surface of the hollow cavity also has electrochemical activity, serving as an additional electrochemical reaction interface, further improving the overall specific capacity of the electrode material.
[0029] This invention also provides a method for preparing a hollow fiber electrode, comprising the following steps: S10. Preparation of graphene / polyaniline composite active materials; S20. Prepare a three-layer coaxial spinning solution, wherein the sheath spinning solution contains thermoplastic polyurethane, graphene / polyaniline composite active material, nano-calcium carbonate and fumed silica thickener, the middle layer spinning solution contains thermoplastic polyurethane, graphene / polyaniline composite active material and polyethylene glycol, and the core layer spinning solution contains thermoplastic polyurethane, graphene / polyaniline composite active material and water-soluble pore-forming agent; S30. Using a three-layer coaxial spinneret, the core layer spinning solution, the intermediate layer spinning solution and the sheath layer spinning solution are simultaneously extruded into a coagulation bath. During the extrusion process, core layer coagulation liquid or inert gas is introduced into the core layer to form a hollow cavity. After phase separation and pore-forming reaction, gradient porous hollow fiber is obtained. S40. The gradient porous hollow fiber is subjected to post-processing and electrochemical deposition.
[0030] The preparation process is green, environmentally friendly, and low-cost. The three-layer coaxial wet spinning technology is mature and can achieve continuous production. Through three-layer coaxial wet spinning, the construction of gradient porous structures and the formation of hollow cavities are completed simultaneously in a single process, eliminating the need for complex post-processing steps and significantly improving preparation efficiency. The graphene / polyaniline composite material is uniformly mixed with thermoplastic polyurethane in the spinning solution, avoiding the problems of weak bonding and easy detachment between the active material and the matrix in traditional coating methods, ensuring the structural stability and durable electrochemical performance of the electrode during repeated bending. By adjusting the composition of each layer of spinning solution (type and content of pore-forming agent, polymer concentration, etc.) and spinning process parameters (feed rate, coagulation bath temperature, etc.), the pore size distribution, porosity, gradient steepness, and inner diameter of the hollow cavity of the gradient porous structure can be precisely controlled to meet different application requirements. The raw material cost is less than 1 / 50 of that of traditional CVD graphene fibers.
[0031] Furthermore, step S10 includes: The graphene / polyaniline composite active material is produced by simultaneous mechanical exfoliation-in-situ polymerization using expanded graphite as raw material and aniline as both an intercalating agent and a polymerization monomer. The material is sheared at a speed of 10,000 rpm to 20,000 rpm for 0.5 h to 2 h in a high-speed shear field, which exfoliates the expanded graphite into graphene and polymerizes aniline in situ on the graphene surface. The mass loading of polyaniline in the graphene / polyaniline composite active material is 30%–60%.
[0032] This invention employs a simultaneous mechanical exfoliation-in-situ polymerization method, eliminating the need for strong acids and oxidants, simplifying the process flow, and combining graphite exfoliation and polyaniline polymerization into a single step, significantly shortening the preparation cycle. Polyaniline grows in situ on the graphene surface, and the two form a tight interfacial bond through π-π conjugation and chemical bonding, resulting in a charge transport efficiency far exceeding that of composite materials prepared by physical mixing methods. The exfoliated few-layer graphene is stably dispersed through interaction with polyaniline via π-π conjugation, effectively preventing the recombination and agglomeration of graphene sheets and ensuring a high specific surface area of the composite material. By adjusting the shearing speed (10000–20000 rpm) and processing time (0.5–2 h), the number of graphene layers, sheet size, and the loading and morphology of polyaniline can be controlled, enabling customized control of the composite material's properties.
[0033] On the other hand, in step S20, the coagulation bath is an acidic aqueous solution containing ammonium persulfate, wherein the concentration of H2SO4 in the acidic aqueous solution is 0.5 M to 2 M, and the concentration of ammonium persulfate is 0.02 M to 0.1 M; the spinning process parameters are: core layer advance rate of 40 mL / h to 60 mL / h, intermediate layer advance rate of 50 mL / h to 70 mL / h, sheath layer advance rate of 70 mL / h to 90 mL / h, and coagulation bath temperature of 20℃ to 30℃. The presence of APS in the coagulation bath allows fiber forming and deep polymerization of aniline to be completed in the same process, eliminating the need for additional post-polymerization treatment steps. By independently adjusting the three-layer feed rate (core layer 40–60 mL / h, intermediate layer 50–70 mL / h, sheath layer 70–90 mL / h), the thickness ratio of each layer and the total fiber diameter can be precisely controlled, thereby regulating the overall morphology of the gradient porous structure. The optimized coagulation bath temperature (20–30℃) ensures a moderate phase separation rate, avoiding both large pores and defects caused by rapid phase separation and fiber deformation caused by slow phase separation, thus guaranteeing good fiber cross-sectional roundness and regular hollow cavities.
[0034] On the other hand, the electrochemical deposition process includes the following steps: S41. Using the gradient porous hollow fiber as the working electrode, place it in a 1M H2SO4 electrolyte containing aniline monomer, and electrochemically deposit a polyaniline nanoarray on the outer surface of the fiber using a constant potential method. S42. The concentration of aniline monomer in the electrolyte is 0.03 M to 0.08 M, the deposition potential is +0.6 V to +1.0 V, and the deposition time is 10 min to 20 min.
[0035] Electrochemically deposited polyaniline nanoarrays form a three-dimensional porous structure on the outer surface of fibers, providing a large number of electrochemically active sites and significantly improving the specific capacity of the electrode. Deposition occurs only on the outer surface of the fiber, while the gradient porous channels (intermediate gradient transition zone) and hollow cavities inside the fiber remain unobstructed, ensuring that the rapid transport of electrolyte ions is not affected—achieving a balance between "high loading on the outer surface" and "fast transport inside." By adjusting the aniline concentration (0.03–0.08 M), deposition potential (+0.6 to +1.0 V), and deposition time (10–20 min), the morphology (nanorings, nanowires, or nanosheets), length, and density of the polyaniline nanoarrays can be precisely controlled, optimizing electrode performance. Electrochemically deposited polyaniline has a higher degree of conjugation and order, and its conductivity is superior to that of chemically synthesized polyaniline, which helps to reduce ohmic polarization of the electrode and improve rate performance.
[0036] Based on the hollow fiber electrode described above, the present invention also provides a flexible capacitor, which includes the hollow fiber electrode, that is, it has all the technical features of the hollow fiber electrode described above, and therefore also has the technical effects brought about by all the technical features described above.
[0037] Please see Figures 2 to 3 The flexible capacitor includes two hollow fiber electrodes 100, and the hollow cavity of the hollow fiber electrode 100 is filled with PVA / H2SO4 gel electrolyte through capillary action. The outer surface of the hollow fiber electrode is coated with a PVA / H2SO4 gel electrolyte layer. The two hollow fiber electrodes are arranged in parallel or intertwined and encapsulated with PDMS or gel electrolyte.
[0038] Gel electrolytes serve as both ion transport media and encapsulation materials, eliminating the need for liquid electrolytes and additional diaphragms. This results in compact device structures with no risk of leakage, making them suitable for wearable electronic device applications. Both the outer surface and inner wall of the fiber electrodes are in contact with the gel electrolyte, enabling them to participate in electrochemical reactions and maximizing the utilization of electrode materials, thus significantly improving the device's energy density. Two fiber electrodes can be arranged in parallel (suitable for planar integration) or twisted together (suitable for linear devices). Combined with flexible encapsulation using PDMS or gel electrolytes, this can meet the diverse device form requirements of various wearable devices. The thermoplastic polyurethane elastic matrix endows the fiber electrodes with excellent flexibility and resilience. Combined with the solid-state properties of the gel electrolyte, the device maintains stable electrochemical performance even under repeated bending, twisting, and other mechanical deformations.
[0039] Similarly, based on the hollow fiber electrode described above, the present invention also provides a flexible battery, which includes the hollow fiber electrode, that is, it has all the technical features of the hollow fiber electrode described above, and therefore also has the technical effects brought about by all the technical features described above.
[0040] The flexible battery includes the hollow fiber electrode 100, which serves as the positive electrode carrier. The outer surface of the hollow fiber electrode 100 is loaded with a ternary composite positive electrode material of graphene / polyaniline / ammonium vanadate. A zinc wire electrode is inserted into the hollow cavity of the hollow fiber electrode 100 to serve as the negative electrode. A ZnSO4 aqueous electrolyte is injected into the hollow fiber electrode to form a flexible battery with a coaxial structure.
[0041] In zinc-ion battery applications, zinc wires can be directly nested within the hollow cavity as the negative electrode, achieving integrated positive electrode material / electrolyte / negative electrode, which greatly simplifies the device assembly process. The utilization rate of active materials is improved. Although the outer layer of dense micropores has low porosity, it has small pore size and large specific surface area. Furthermore, the electrodeposited PANI nanoarray is uniformly distributed on the outer surface, ensuring sufficient contact between the active material and the electrolyte. The utilization rate of active materials is increased from 30-50% in traditional uniform pore structures to 60-75%.
[0042] Based on the above-mentioned hollow fiber electrode and its preparation method, flexible capacitor, and flexible battery, the present invention provides the following embodiments.
[0043] Example 1: Fabrication of a gradient porous hollow fiber electrode (1) Preparation of Graphene / PANI composite material: 10 g of expanded graphite powder (40 μm grade) and 100 g of aniline monomer were dispersed in 2 L of ethanol and ultrasonically pre-dispersed for 30 min. 500 mL of pre-cooled 1 M H2SO4 solution was added, and the mixture was sheared at 15000 rpm for 1 h in a high-speed shear disperser. Subsequently, 500 mL of 1 M H2SO4 solution containing 125 g of ammonium persulfate (APS) was added, and shearing was continued for 1 h. The product was repeatedly washed with deionized water and purified by centrifugation to obtain a Graphene / PANI composite aqueous dispersion.
[0044] (2) Preparation of spinning solution: Thermoplastic polyurethane (PU, BASF 1185A) was dissolved in DMF and stirred at 85℃ for 3 h. Spinning solutions were prepared according to the three-layer formula: sheath layer (15 wt% PU / DMF + 20 wt% Graphene / PANI + 3 wt% nano CaCO3 + 0.5 wt% fumed SiO2 thickener), intermediate layer (15 wt% PU / DMF + 35 wt% Graphene / PANI + 10 wt% PEG-4000), and core layer (8 wt% PU / DMF + 15 wt% Graphene / PANI + 10 wt% NaCl pore-forming agent). Each layer of spinning solution was ultrasonicated for 2 h, high-speed sheared for 2 h (ice-water bath), and vacuum degassed for 12 h before use.
[0045] (3) Three-layer coaxial wet spinning: A customized three-layer coaxial spinneret was used (the channel diameters for the core layer / intermediate layer / sheath layer were 0.3 / 0.6 / 1.0 mm, respectively). The core layer feed rate was 50 mL / h (with 1 M H2SO4 coagulation solution introduced), the intermediate layer 60 mL / h, and the sheath layer 80 mL / h. The coagulation bath was a 1 M H2SO4 + 0.05 M APS solution at 25℃. The spun nascent fibers remained in the coagulation bath for 5 min.
[0046] (4) Post-treatment: The fiber was repeatedly washed with deionized water to remove DMF, PEG and NaCl, and then vacuum dried at 60℃ for 12 h. It was then immersed in acetone for 30 min to remove residual PEG and pore-forming agent byproducts, and vacuum dried again to obtain gradient porous hollow fiber (GPHF-v2).
[0047] (5) Electrochemical deposition optimization: Prepare 1 M H2SO4 electrolyte with 0.05 M aniline monomer, use GPHF-v2 as working electrode, Pt sheet as counter electrode, and Ag / AgCl as reference electrode, electrochemically deposit PANI for 15 min at a constant potential of +0.8 V to obtain the optimized gradient porous hollow fiber electrode (E-GPHF-v2).
[0048] Example 2: Assembly and Performance Testing of Flexible Capacitors Two E-GPHF-v2 electrodes were arranged in parallel, and a PVA / H2SO4 gel electrolyte (5 g PVA dissolved in 50 mL of 1 M H2SO4, stirred at 85℃ for 3 h) was injected into the hollow cavity of the fiber via capillary action. Simultaneously, the gel electrolyte was coated onto the outer surface of the fiber. After drying at 40℃ for 24 h, the fiber was encapsulated with a PDMS film to obtain an all-solid-state symmetrical flexible SC. Test results showed that at a current density of 0.3 mA / cm, the specific capacitance reached 980 mF / cm, the energy density was 52 μWh / cm², and the power density was 650 μW / cm². Under 50% tensile deformation, the capacitance retention was >92%, and after 15,000 cycles, the capacitance retention was >88%. The dense microporous region of the outer layer effectively protected the internal structure, and the fiber surface remained intact after cycling tests.
[0049] Example 3: Assembly and performance testing of aqueous zinc-ion batteries A 150 μm diameter zinc wire was inserted into the hollow cavity of the GPHF-v2 fiber as the negative electrode, and the outer surface of the fiber was coated with Graphene / PANI / NH4V4O. 10 (GPNVO) ternary composite cathode material slurry was prepared and dried, and a coaxial flexible aqueous zinc-ion battery was assembled using 3 M ZnSO4 aqueous solution as the electrolyte. Test results showed that at a current density of 0.1 A / g, the specific capacity reached 580 mAh / g, and 72% of the capacity was retained at 2 A / g. After 2000 cycles, the capacity retention was >82%, and at -20℃, the specific capacity retention was >58%. The design of nested zinc wires within the hollow cavity significantly simplified device assembly while ensuring close contact between the zinc anode and cathode materials.
[0050] Example 4: Comparison with existing technologies Under the same test conditions, the gradient porous hollow fiber electrode (GPHF-v2) of the present invention was compared with the original scheme's external macroporous and internal microporous structure fiber electrode (GPHF-v1). The results showed that: (1) Mechanical properties: The tensile strength (45 MPa) of GPHF-v2 was significantly better than that of GPHF-v1 (28 MPa), and the capacitance retention rate after 10,000 cycles of 50% tensile stress was much higher for GPHF-v2 (88%) than that for GPHF-v1 (50%); (2) Specific capacitance: GPHF-v2 (980 mF / cm) was slightly lower than that of GPHF-v1 (1200 mF / cm), but its overall performance (energy density 52 μWh / cm) was better. 2 vs 60 μWh / cm 2 (3) Surface integrity: After cyclic testing, no visible cracks were found on the surface of GPHF-v2, while obvious cracks and peeling appeared on the surface of GPHF-v1. This solution sacrifices a small amount of specific capacitance in exchange for significantly improved mechanical durability and cyclic stability, making it more suitable for long-term wearable applications.
[0051] The above are merely preferred embodiments of the present invention and do not limit the scope of the patent. Any equivalent structural or procedural transformations made based on the description and drawings of the present invention, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of the present invention.
Claims
1. A hollow fiber electrode, characterized in that, The hollow fiber electrode comprises, from the outside to the inside, the following components along the radial direction: The outer dense microporous region has a pore size of 1 nm to 10 nm and a porosity of 10% to 30%, and the outer dense microporous region forms a mechanical protective layer; An intermediate gradient transition region, wherein the pore size continuously transitions from 5nm to 10nm on the outer side to 50nm to 200nm on the inner side, forms an ion transport channel; and, An inner wall layer, in which a hollow cavity is formed, the inner diameter of which is 50μm to 200μm, is used to fill a gel electrolyte or to accommodate a zinc wire electrode. The hollow fiber electrode is made of graphene / polyaniline composite active material and thermoplastic polyurethane elastic matrix.
2. The hollow fiber electrode according to claim 1, characterized in that, The outer dense microporous region is formed by phase separation of the sheath spinning solution, which contains nano-calcium carbonate and fumed silica thickener. The nano-calcium carbonate has a particle size of 20 nm to 100 nm, and the mass of the nano-calcium carbonate is 2% to 5% of the total mass of the sheath spinning solution; the mass of the fumed silica is 0.3% to 0.8% of the total mass of the sheath spinning solution.
3. The hollow fiber electrode according to claim 1, characterized in that, The intermediate gradient transition zone is formed by phase separation of the intermediate layer spinning solution, and the intermediate layer spinning solution contains a polyethylene glycol pore-forming agent. The polyethylene glycol has a molecular weight of 2000 to 8000, and the mass of the polyethylene glycol is 8% to 15% of the total mass of the intermediate spinning solution.
4. The hollow fiber electrode according to claim 1, characterized in that, The inner wall layer is formed by phase separation of the core spinning solution. The core spinning solution contains a water-soluble pore-forming agent selected from sodium chloride or sodium bicarbonate. The mass of the water-soluble pore-forming agent is 8% to 15% of the total mass of the core spinning solution.
5. A method for preparing a hollow fiber electrode, characterized in that, Includes the following steps: Preparation of graphene / polyaniline composite active materials; A three-layer coaxial spinning solution was prepared, wherein the sheath spinning solution contains thermoplastic polyurethane, graphene / polyaniline composite active material, nano-calcium carbonate and fumed silica thickener; the middle layer spinning solution contains thermoplastic polyurethane, graphene / polyaniline composite active material and polyethylene glycol; and the core layer spinning solution contains thermoplastic polyurethane, graphene / polyaniline composite active material and water-soluble pore-forming agent. The core spinning solution, intermediate spinning solution and sheath spinning solution are simultaneously extruded into a coagulation bath using a three-layer coaxial spinneret. During the extrusion process, core coagulation solution or inert gas is introduced into the core layer to form a hollow cavity. After phase separation and pore-forming reaction, gradient porous hollow fiber is obtained. The gradient porous hollow fiber is subjected to post-processing and electrochemical deposition.
6. The method for preparing a hollow fiber electrode according to claim 5, characterized in that, The steps for preparing the graphene / polyaniline composite active material include: The graphene / polyaniline composite active material is produced by simultaneous mechanical exfoliation-in-situ polymerization using expanded graphite as raw material and aniline as both an intercalating agent and a polymerization monomer. The material is sheared at a speed of 10,000 rpm to 20,000 rpm for 0.5 h to 2 h in a high-speed shear field, which exfoliates the expanded graphite into graphene and polymerizes aniline in situ on the graphene surface. The mass loading of polyaniline in the graphene / polyaniline composite active material is 30%–60%.
7. The method for preparing a hollow fiber electrode according to claim 5, characterized in that, In the step of simultaneously extruding the core spinning solution, intermediate spinning solution, and sheath spinning solution into a coagulation bath using a three-layer coaxial spinneret, the coagulation bath is an acidic aqueous solution containing ammonium persulfate, wherein the concentration of H2SO4 in the acidic aqueous solution is 0.5 M to 2 M, and the concentration of ammonium persulfate is 0.02 M to 0.1 M. The spinning process parameters are as follows: core layer advance rate is 40 mL / h to 60 mL / h, intermediate layer advance rate is 50 mL / h to 70 mL / h, sheath layer advance rate is 70 mL / h to 90 mL / h, and coagulation bath temperature is 20℃ to 30℃.
8. The method for preparing a hollow fiber electrode according to claim 5, characterized in that, The steps of the electrochemical deposition process include: The gradient porous hollow fiber was used as the working electrode and placed in a 1M H2SO4 electrolyte containing aniline monomer. A polyaniline nanoarray was electrochemically deposited on the outer surface of the fiber using a constant potential method. The concentration of aniline monomer in the electrolyte is 0.03 M to 0.08 M, the deposition potential is +0.6 V to +1.0 V, and the deposition time is 10 min to 20 min.
9. A flexible capacitor, characterized in that, The device comprises two hollow fiber electrodes as described in any one of claims 1 to 4, wherein the hollow cavity of the hollow fiber electrode is filled with PVA / H2SO4 gel electrolyte by capillary action, and the outer surface of the hollow fiber electrode is coated with a PVA / H2SO4 gel electrolyte layer. The two hollow fiber electrodes are arranged in parallel or intertwined and encapsulated with PDMS or gel electrolyte.
10. A flexible battery, characterized in that, The device includes a hollow fiber electrode as described in any one of claims 1 to 4, wherein the hollow fiber electrode is a positive electrode carrier, the outer surface of the hollow fiber electrode is loaded with a graphene / polyaniline / ammonium vanadate ternary composite positive electrode material, a zinc wire electrode is inserted into the hollow cavity of the hollow fiber electrode as a negative electrode, and a ZnSO4 aqueous electrolyte is injected into the hollow fiber electrode to form a flexible battery with a coaxial structure.